Characteristics of Lower Urinary Tract Symptoms (LUTS) in the Chronic Disease Management Program (Program Pengelolaan Penyakit Kronis, PROLANIS) Patients: A Pilot Study in Gorontalo Province - Ibrahim, Sri A; Hasanuddin, Abdi Dzul Ikram (Universitas Negeri Gorontalo, 2024)
Introduction: Lower Urinary Tract Symptoms (LUTS) are common in older adults and significantly impact individuals, caregivers, and the broader healthcare system. As the elderly population with various comorbidities increases, the burden of LUTS will increase. The chronic disease management program (Program Pengelolaan Penyakit Kronis, PROLANIS) is a government program generally followed by the elderly. This study aims to describe the characteristics of LUTS in PROLANIS patients in Gorontalo Province.Methods: The analytical observational study design, using a cross-sectional approach, was conducted on PROLANIS patients living in rural and urban areas in Gorontalo Province is between July - October 2023. An incidental sampling technique was conducted on eligible patients and areas. LUTS symptoms were measured using the International Prostate Symptom Score (IPSS) questionnaire and categorized into mild, moderate, and severe. LUTS symptoms were considered significant if the IPSS score was ≥8.Results: Of the 52 participants, 38.50% experienced significant LUTS symptoms. The majority of symptoms felt were nocturia (score two, as many as 23.10%) and mild symptoms (53.80%). Geographical differences, gender, education level, and age were not associated with LUTS symptoms (p 0.10).Conclusion: The prevalence of LUTS in patients undergoing PROLANIS is relatively high. The majority of LUTS patients have mild symptoms, with nocturia being the most common complaint compared to other symptoms. Further studies with a larger sample size and involving multiple sites are needed to obtain a more valid description of the characteristics of LUTS epidemiology in the PROLANIS population. Keywords: Aged; Disease Management; Lower Urinary Tract Symptoms; Nocturia